Hotel San Jose site. - Gordon, John C. (photographer):::Creator::::::::::::
"This is the corner of West Santa Clara and Notre Dame Streets about 1930." Hotel San Jose's name was changed to the De Anza Hotel before its construction. Photograph shows the future construction site of the De Anza Hotel with automobiles lining the street.